Carrot seed production under different soil moisture regimes - Marquelli, Waldir A.; Oliveira, Carlos A.S.; Silva, Washington L.C. (Pesquisa Agropecuaria Brasileira, 2014)
Field experiments were carried out at CNPH-EMBRAPA in 1984, 1985, and 1986 with the objective of establishing soil moisture management for carrot (Daucus carota L.) seed production, based on soil water tension. Treatments consisted of refilling the root zone with water as soil water tension reached values of 25, 50, 100, 200, 400, 800 and 1.500 kPa, at 10 cm depth till flowering and at 20 cm depth after that phase. Regression analysis allowed to conclude that maximum seed productivity was obtained when irrigation was applied each time soil water tension reached 75 kPa. Economical water tension was found to be 80 kPa. Stand, germination and weight of 1.000 seeds were found not to be significantly influenced by the treatments
Keywords: Daucus carota; soil water tension; irrigation